2003
DOI: 10.1145/960492.960540
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the educational impact of visualization

Abstract: The educational impact of visualization depends not only on how well students learn when they use it, but also on how widely it is used by instructors. Instructors believe that visualization helps students learn. The integration of visualization techniques in classroom instruction, however, has fallen far short of its potential. This paper considers this disconnect, identifying its cause in a failure to understand the needs of a key member in the hierarchy of stakeholders, namely the instructor. We describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 14 publications
1
37
0
1
Order By: Relevance
“…The lack of improvement in correct responses to the recall and transfer tests, shows an increase in student understands of these fundamental concepts were not detected. This supports the view that 'continuous animation offers no real advantage to achieve more effective student understanding of complex computer concepts [20,21].It is therefore considered possible that CD animations included with textbooks, or on-line links to multi-media resources, will not necessarily improve student understanding above that expected from a static diagram. The analysis revealed that the high prior knowledge group of students that viewed the 2-D version showed statistical differences in the recall score, where they performed better compared to the students who viewed the 3-D version.…”
Section: Discussionmentioning
confidence: 52%
“…The lack of improvement in correct responses to the recall and transfer tests, shows an increase in student understands of these fundamental concepts were not detected. This supports the view that 'continuous animation offers no real advantage to achieve more effective student understanding of complex computer concepts [20,21].It is therefore considered possible that CD animations included with textbooks, or on-line links to multi-media resources, will not necessarily improve student understanding above that expected from a static diagram. The analysis revealed that the high prior knowledge group of students that viewed the 2-D version showed statistical differences in the recall score, where they performed better compared to the students who viewed the 3-D version.…”
Section: Discussionmentioning
confidence: 52%
“…The above citation from Stern et al supports the observation that there is a common belief among engineering instructors that visualization tools enhance students' understanding of engineering principles and their application to problems [8,9]. However, existing research provides little evidence to support this belief.…”
Section: Introductionmentioning
confidence: 93%
“…The reason for this usage pattern is possibly that teachers face substantial impediments when they try to use such visualization tools in their teaching [14]. Hence, an effective way to increase the use of dynamic visualization in classrooms is to develop and disseminate standalone interactive simulations which are suited to a curriculum [7]. This would facilitate easy and widespread access to high quality educational resources such as PhET [4], MyPhysicsLab [15], cITe [16].…”
Section: Motivationmentioning
confidence: 99%
“…So teachers prefer to create their own content to use in classroom. If a teacher could develop the content in minimum time, then this would encourage them to use more simulations in their classrooms [7]. The three key obstacles to widespread adoption of interactive simulations in classroom are:…”
Section: Introductionmentioning
confidence: 99%